Comparison between open-site and below-canopy climatic conditions in Switzerland for different types of forests over 10 years (1998-2007) - Renaud, Valentine; Innes, J. L.; Dobbertin, Matthias; Rebetez, Martine (My University, 2011)
We compared below-canopy and open-site climatic conditions for 14 different forest sites in Switzerland and analysed the forest influence on local summer and winter climate according to the forest type (coniferous, mixed, deciduous), soil type, slope orientation, basal area and tree height. We compared below-canopy and open-field data for minimum, maximum and daily mean temperature, relative humidity, maximum and daily mean photosynthetically active radiation (PAR) and wind speed from 1998 to 2007. We found clear differences between below-canopy and open-field temperatures, humidity, wind speed and PAR and could relate them to the specific site conditions and forest type. The forest influence on PAR and maximum temperature is clearly determined by the forest type, whereas the influence on minimum temperature is affected by both forest type and slope orientation and impact on humidity depends on the soil type. The wind speed is most impacted by topography and slope orientation.